INTEGRATION OF CONSTRUCTIVISM IN PROJECT LEARNING AT ELEMENTARY SCHOOL LEVEL - Booby Akbar; Ihsan Hanafi (Cattleya Darmaya Fortuna, 2025)
This study aims to investigate the role of constructivism philosophy in the implementation of Project-Based Learning (PjBL) model at primary school level. Currently, many of the teaching methods used are still conventional, leaving less room for students to be active in constructing their knowledge. The method used in this research is descriptive qualitative with a literature study approach, which analyzes various sources to deeply understand how constructivism is applied in PjBL. The results show that constructivism changes the perspective of education by making students the main actors in the learning process. The PjBL model provides real opportunities for students to not only receive information, but also to construct knowledge through direct experience, exploration, and interaction with their peers. This research also found that the role of the teacher changes from being a conveyor of information to a facilitator who creates a learning atmosphere that supports active learning. The main contribution of this research is an in-depth explanation of the relationship between constructivism and PjBL in primary schools. This model is proven to be effective in promoting creativity, critical thinking and learning independence among students. With a student-centered approach, they can develop process skills, collaboration and practical problem-solving abilities.